Animal learning media in nurturing literacy of elementary school children using QR-Code technology - Paulina Erawati Paramita; Firman Aziz; Nana Citrawati Lestari (Sean Institute, 2024)
Education is a critical component in a nation's progress and must be modified to accommodate technological advancements. QR Code is a contemporary trending technology that has the potential to streamline the learning process and promote students' literacy development when implemented in the classroom. The implementation of QR-Code technology in elementary school literacy instruction yields substantial advantages, including enhanced information accessibility, promotion of digital literacy proficiency, and heightened student engagement with the learning process. Therefore, in order to enhance the quality of literacy education at the primary level, it is urgent to conduct research and develop learning methods that incorporate QR-Code technology into the context of literacy instruction for elementary school students.